PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD NEGERI 009 BINIO JAYA - Sabrianti Sabrianti; Otang Kurnaiman; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this research is the low student learning outcomes. The low student learning outcomes are caused by several factors among which teachers do not use a variety of learning models. It can be seen from the symptoms seen in students in the learning process that the students are not active in learning, students are not able groups, and students are less able to appear in the classroom. Based on the problems it is necessary to find a way to solve problems. Among them is by applying the learning model that can encourage students to become more active in learning and being able to group. Cooperative learning model types think pair share can provide opportunities for students to be active in learning and mutual sharing with another group of friends who can drive the learning outcomes of fourth grade students of SD Negeri 009 Binio Jaya. Subjects in this study were fourth grade students of SD Negeri 009 Binio Jaya academic year 2014/2015 the number of students 32 people. This research was conducted in two cycles with four meetings and two replications end. Data collection instruments in this study was the observation sheet student, teacher observation sheets, and daily tests test cycle. The study is in the form of classroom action research (PTK), aims to improve student learning outcomes Binio Jaya Elementary School 009 in the material development of production technology and the development of communication technology. These results indicate that cooperative learning model Think Pair Share can improve learning outcomes Elementary School fourth grade students 009 Binio Jaya. Increased student learning outcomes can be seen from the increase in base score with an average value of 58.75 with less category, the first cycle with an average of 70.31 with good category, and the second cycle the average value of 80.00 with both categories. Evident from the average score of the base, the first cycle and second cycle increase occurred in the first cycle of 19.67% and experienced a significant increase seen in the second cycle of 36.17%. This means that the cooperative learning model Think Pair Share can improve learning outcomes Elementary School fourth grade students 009 Binio Jaya.Keywords: Cooperative Learning Model Think Pair Share